Use of Micro-CT Imaging to Assess Ventral Mandibular Cortical Thickness and Volume in an Experimental Rodent Model With Chronic High-Phosphorus Intake - Jekl, Vladimir; Brinek, Adam; Zikmund, Tomas; Jeklova, Edita; Kaiser, Josef (Frontiers in Veterinary Science, 2021)
Adverse effects of high dietary phosphorus on bone health have been observed in both animal and human studies. The aim of the investigation was to examine chronic effect of high phosphorus diet on the apical mandibular cortical thickness and volume in a hystricomorph rodent (Octodon degus) using micro-computed tomography. Male degus were randomly divided into two groups fed by different mineral content from the age of 12 weeks till the age of 17 months. The micro-CT scanning, and wall thickness analysis was applied on region of the mandible exactly under the apices of the 4th premolar tooth, first and second molar tooth in 2 animals from each group. General overview and mapping of the ventral mandibular bone thickness revealed pronounced bony mandibular protrusions in all the animals fed a high-phosphorus diet with obvious bone thinning apically to the 4th premolar and first and second molar teeth apices. Mandibular bone volume and thickness located apically to the premolar and molars were statistically significantly smaller/thinner in group fed by high phosphorus diet. The thinnest bone measured 0.004 mm, where the 4th premolar tooth almost perforated mandibular cortex. The influence of different environmental, infectious, or metabolic factors on the growing tooth, alveolar bone formation, and bone pathologies must be done experimentally on growing animals. In contrast, degus have continuously growing dentition, and the effect of any of the above listed factors can be studied in this animal model at any age and for longer time periods.